1976
DOI: 10.1242/jcs.22.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Classification of loops of lampbrush chromosomes according to the arrangement of transcriptional complexes

Abstract: The arrangement of transcriptional units in the loops of lampbrush chromosomes from oocyte nuclei of urodele amphibia and from primary nuclei of the green alga Acetabularia have been studied in the electron microscope using spread preparations. Loops with different patterns of arrangement of matrix units (i.e. to a first approximation, transcriptional units) can be distinguished: (i) loops consisting of one active transcriptional unit; (ii) loops containing one active transcriptional unit plus additional fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Another scenario - many genes of different polarity transcribed in a single lateral loop and separated by a chromatin knot (Figure 6) or even one by one without visible chromatin knots (Figure S9). Such arrangement of transcriptional units in lampbrush lateral loops completely corresponds to the classification of lateral loops in amphibian lampbrush chromosomes suggested according to electron-microscope observations of spread chromatin (Scheer et al . 1976).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Another scenario - many genes of different polarity transcribed in a single lateral loop and separated by a chromatin knot (Figure 6) or even one by one without visible chromatin knots (Figure S9). Such arrangement of transcriptional units in lampbrush lateral loops completely corresponds to the classification of lateral loops in amphibian lampbrush chromosomes suggested according to electron-microscope observations of spread chromatin (Scheer et al . 1976).…”
Section: Resultssupporting
confidence: 84%
“…2016; Morgan 2018). This is most likely achieved by the tight coverage of transcribed genes by elongating RNA polymerases as shown by chromosome spreading according to the Miller technique (Scheer et al . 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibile relationship of DNA loops to transcriptional units has also been extensively discussed (Georgiev et al, 1978) . While the only definitive evidence for the organization of transcriptional units into distinct loops is derived from the specialized lampbrush chromosome systems (Scheer et al, 1979) , concluded that transcriptional sequences are arranged in a specific manner along the DNA loops in HeLa cells, and Pardoll & Vogelstein (1980) reported an enrichment in ribosomal RNA sequences in matrix-attached DNA. Our hybridization analysis indicates that transcribed sequences are randomly associated with attachment sites, though it is still an open question as to whether transcriptional units are arranged into specific orientations along the DNA loops during the actual process of transcription.…”
Section: Discussionmentioning
confidence: 99%